2023
DOI: 10.1136/bmjopen-2022-062098
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Peripheral Arterial Tonometry (Endo-PAT 2000) use in paediatric patients: a systematic review

Abstract: ObjectivesEndo Peripheral Artery Tonometry (EndoPAT-2000) is a non-invasive technology for measuring endothelial dysfunction (ED). The reactive hyperaemia index (RHI) is resulted and is low when ED is present. We aim to synthesise the literature on paediatric ED that used Endo-PAT analysis.DesignA comprehensive systematic review was conducted from January 2015 to March 2021. The databases included Cochrane, MEDLINE EBSCO, EMBASE (Ovid), PUBMED and CINAHL EBSCO. Exclusion criteria were: (1) If a study used a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Other methods include the use of external control arms as an alternative to placebo. 21 , 22 However, establishing historical control groups is challenging in this field due to the frequent introduction of new treatments, and increasing inclusion of patients who have failed multiple therapies into clinical trials. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Other methods include the use of external control arms as an alternative to placebo. 21 , 22 However, establishing historical control groups is challenging in this field due to the frequent introduction of new treatments, and increasing inclusion of patients who have failed multiple therapies into clinical trials. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The first option to assess ED is flow-mediated dilatation (FMD), where ED is characterized by less vasodilatation (reduced FMD) in the brachial artery. FMD is assessed using ultrasound to measure changes in brachial artery diameter in response to increased flow after a period of vascular occlusion caused by a blood pressure cuff and is highly dependent on NO bioavailability [ 23 ]. Endo-PAT 2000 is a newer, non-invasive technology for measuring ED.…”
Section: Methods Of Assessing Edmentioning
confidence: 99%
“…Hayden et al, in their recent study, reported that Endo-PAT was an easy test to conduct and well-tolerated by children and adolescents with T1DM, and it could be performed at the point of care [ 23 ]. Two studies reported lower RHI results in T1DM [ 26 , 27 ].…”
Section: Methods Of Assessing Edmentioning
confidence: 99%
“…AI correct values are between -30% and -10% with a mean intra-individual variability of 37%. EndoPat could be useful in recognizing patients at the earliest stage of CVD, showing vascular disfunction in patients with DM, familiar hypercholesterolemia, obesity, inflammatory bowel disease, Fontan survivors, and could monitor the effects of metformin and sulfonylurea treatment [2,5]. Despite many advantages, availability of the equipment is limited.…”
mentioning
confidence: 99%
“…Evaluation of endothelial function is also possible using the non-invasive, fast (15 minutes), and non-operator-dependent EndoPat, which enables detection of endothelial dysfunction based on the registration of changes occurring in the digital pulse wave (peripheral arterial tone, PAT), measured using a pair of plethysmographic probes placed on the index fingers of each hand. Endothelial-mediated alterations in the PAT signal are induced by generating a downstream hyperemic response [ 2 , 5 ].…”
mentioning
confidence: 99%